Pelatihan Penggunaan Aplikasi Mendeley dalam Menyusun Karya Tulis Ilmiah Bagi Guru - Sitti Rahmaniar Abubakar; Muhamad Safiuddin Saranani; Ahid Hidayat; Arvyaty Arvyaty; Afifah Nur Hidayah; Sri Yuliani; Asrun Safiuddin; Damsir Dima; Nur Aeni Muhlisa Dhafet (Yumary: Jurnal Pengabdian kepada Masyarakat, 2026)
Purpose: Mendeley is an application widely used by scientific article writers. With the Mendeley application, writers will be assisted in citing and compiling reference lists. Training in the use of the Mendeley application in compiling scientific papers for teachers in Kendari City aims to improve teachers' understanding and skills in reference and citation management. Research Methodology: The activity was conducted through interactive lectures, demonstrations of Mendeley usage, and hands-on practice Results: The results of the activity showed that the training participants, consisting of teachers in Kendari City, experienced a significant increase in their understanding of the importance of citations and their practical skills in using Mendeley to manage references, insert citations, and automatically generate bibliographies. This community service activity was motivated by the low proficiency of teachers in writing scientific papers that meet academic writing standards, particularly regarding citations and bibliographies. Conclusions: The training on the use of Mendeley for teachers successfully improved their understanding and basic skills in digital reference management. Participants were able to operate key features such as automatic citation and bibliography generation Limitations: Limited training time, varying levels of digital literacy, and technical device issues posed challenges Contributions: This training is expected to encourage teachers to be more active in scientific activities and produce high-quality scientific papers.